(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2024)
The study of professional genres in the field of education is crucial for the management of knowledge in educational centers, as well as for understanding the broader pedagogical cultural practices in which the Spanish language is deployed in active use. In this context, the purpose of this paper is to describe the rhetorical organization of the didactic guide discursive genre of the professional teaching field, based on the analysis of the situated genre as a theoretical-analytical tool. The self-compiled textual corpus is composed of 128 teaching guides used in Chilean classrooms and written by secondary school teachers. The textual description, in turn, is complemented with ethnographic information from an in-depth interview with a teacher of recognised prestige in the classroom. The findings allow us to configure a discursive rhetorical model composed of four moves and 14 steps. Likewise, the analysis of the data shows the high flexibility of the genre and its possibilities of adaptation to different classroom contexts and to changes in the educational system. Finally, some implications for professional literacy and instructional design are discussed.